The Dynamic Correlation between ASEAN-5 Stock Markets and World Oil Prices - Robiyanto Robiyanto (Jurnal Keuangan dan Perbankan, 2018)
Various studies on the relationship between world oil prices and stock markets that have been done previously mostly still done by using a static approach or an approach to test whether there is a short-term or long-term relationship. This research scrutinizes the dynamic relationship between world oil price change with the return of ASEAN’s main stock markets such as Indonesia, Singapore, Malaysia, the Philippines, and Thailand by using Dynamic Conditional Correlation-Generalized Autoregressive Conditional Heteroscedasticity (DCC-GARCH). The result shows that the correlation between world oil price’s change with the return of ASEAN’s main stock market was not static but change according to the stock market and the commodity market’s condition. During the normal period, DCC-GARCH is in the narrow range and stable, but during the period of stock market and commodity market turbulence, DCC-GARCH could alter extremely from positive to negative in some ASEAN countries. Generally, it is concluded that the use of a static approach was not appropriate especially for rapidly changing in the financial market and commodity market.JEL Classification: G10; G15; Q41DOI: https://doi.org/10.26905/jkdp.v22i2.1688